Plastic stress intensity factor behavior at small and large scale yielding - Alexander Zakharov; Valery Shlyannikov; Anastasia Tartygasheva (Fracture and Structural Integrity)
In this paper the plastic stress intensity factor (SIF) is used to study the coupling effects of the loading biaxiality, the material properties and the cracked body configuration in both the small- and large-scale yielding ranges. A finite element (FE) analysis is performed for a cracked Mode I plane strain plate subjected to biaxial tension/compression loading. The governing parameter of the elasticplastic crack-tip stress field In-integral at the crack tip, the J-integral, and the plastic SIF, are calculated as a functions of the loading biaxiality and the applied stress levels. The different trend of the In-integral distributions as a function of the applied stresses with respect to the J-integral is demonstrated. The contrary character of the distributions of the plastic SIF and the J-integral as a function of the biaxial stress ratio is observed. Special emphasis is put on the behavior of the J-integral and the plastic SIF for the specified test specimen geometries under mixed mode loading. The coupling effects of the mixed mode fracture and the material properties on the J-integral and the plastic SIF distributions for a set of the specimen configurations are stated. Comparative analysis of the values of the plastic SIF calculated for both small-scale and large-scale yielding in the test specimen configurations considered here is presented. A significant difference between the small- and the large-scale yielding plastic SIF in the full range of mixed modes is shown.